In vitro Fermentation Characteristics and Rumen Microbial Population of Diet Supplemented with Saccharomyces cerevisiae and Rumen Microbe Probiotics - Lilis Riyanti; . Suryahadi; Dwierra Evvyernie (Media Peternakan, 2016)
The objective of this study was to select three strains of probiotic Saccharomyces cerevisiae and to evaluate the effect of S. cerevisiae and rumen bacteria isolate (MR4) supplementation and their combination on rumen fermentability and rumen microbial population. Experiment 1 was designed in a 4 x 5 factorial randomized block design with 3 replications. The first factor was S. cerevisiae strain consisted of control treatment (without S. cerevisiae supplementation), NBRC 10217, NRRL Y 567 and NRRL 12618, and the second factor was incubation time consisted of 0, 1, 2, 3, and 4 h. Ration was basal ration for feedlot with forage to concentrate ratio (F:C)= 60:40. Dosage of each treatment with S. cerevisiae was 5 x 1010 cfu/kg ration. Experiment 2 was designed in randomized block design with 4 treatments: P0= basal ration of feedlot; P1= P0 + S. cerevisiae; P2= P0 + MR4 isolate (5 x 107 cfu/kg ration); P3= P0 + S. cerevisiae and MR4 isolate. The result of experiment 1 showed that supplementation of S. cerevisiae NRRL 12618 had the highest S. cerevisiae population and increased rumen bacterial population. This strain was selected as probiotic in experiment 2. The result from experiment 2 showed that probiotic supplementation stabilized rumen pH and produced the highest NH3 concentration (P<0.05) and bacterial population (P<0.05). As compared with control, all treatments reduced protozoa population (P<0.05). Combination of S. cerevisiae and MR4 probiotics produced the highest total volatile fatty acids (VFA) and isovalerate (P<0.05). It was concluded that strain S. cerevisiae NRRL 12618 had potential as probiotic yeast. Supplementation with this strain increased fermentability, rumen isoacid and decreased A:P ratio. Those abilities could be improved with MR4 rumen isolate probiotic.